2008
DOI: 10.1123/tsp.22.1.73
|View full text |Cite
|
Sign up to set email alerts
|

Athletes’ Perceived Use of Information Sources When Forming Initial Impressions and Expectancies of a Coach: An Explorative Study

Abstract: The study aimed to identify the sources of information that athletes perceive as influential during their initial evaluation of coaching ability. University athletes (N = 538) were asked to indicate the influence of 31 informational cues (e.g., gender, body language or gestures, reputation) on the initial impression formed of a coach. Following exploratory factor analysis, a 3-factor model (i.e., static cues, dynamic cues, and third-party reports) was extracted. Mean scores revealed that although static cues (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
30
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 32 publications
6
30
0
1
Order By: Relevance
“…Optimising perceptions of leaders in the media may be particular worthwhile in light of the impression formation literature (Manley et al 2008). For example, a number of strategies were displayed 30 that sought to create a team identity at London 2012.…”
Section: Discussionmentioning
confidence: 99%
“…Optimising perceptions of leaders in the media may be particular worthwhile in light of the impression formation literature (Manley et al 2008). For example, a number of strategies were displayed 30 that sought to create a team identity at London 2012.…”
Section: Discussionmentioning
confidence: 99%
“…This is because, provided a strong sense of social identity can be maintained in the context of dealing with these challenges, athletes should derive positive self-esteem, receive support, and collaborate with others to resist stressors, thus increasing the likelihood that they will be able to cope with (and adjust to) these various challenges. Evidence that social identity and self-categorization processes structure social influence within groups [30] also leads us to expect that the social identity approach could be used to better understand the dynamics of (a) the coach-athlete relationship (with outcomes depending on the evolving nature of their shared identity) [128], (b) coach-athlete attributional divergence and conflict [187,188], (c) sports-related impression formation [189], (d) sports communication [190], and athletes' and fans' affective states and emotional contagion [191].…”
Section: New Frontiers: Towards a Broader Application Of The Social Imentioning
confidence: 99%
“…Regardless, past research has shown that a coach's presentation style is very important. A study done by Manley et al (2008) on athletes' perceived use of information sources when forming initial impressions and expectancies of a coach showed that out of 31 informational cues, the dynamic cues (e.g., eye contact, tone of voice, body language, clarity of voice, language, etc.) and third-party reports about a coach (e.g., coaching experience, qualifications, etc.)…”
Section: Journal Of Coaching Educationmentioning
confidence: 99%